Incidence of influenza virus infection among pregnant women: a systematic review - Katz, MA; Gessner, BD; Johnson, J; Skidmore, B; Knight, M; Bhat, N; Marshall, H; Horne, DJ; Ortiz, JR; Fell, DB (BioMed Central, 2017)
BACKGROUND: The World Health Organization (WHO) considers pregnant women to be a risk group for severe influenza disease. We conducted a systematic review to evaluate influenza disease incidence in pregnant women in order to inform estimates of influenza vaccine impact for low-resource countries. METHODS: We performed electronic literature searches, targeting studies on the following outcomes in pregnant women: attack rate, hospitalization rate, intensive care unit admission rate, mortality rate, and disability-adjusted life years lost. Only original studies published in peer-reviewed journals that had laboratory confirmation for influenza virus infection and included population-based incidence rates with denominator data were included. We summarized study characteristics in descriptive tables and outcome-specific Forest plots. We generated summary incidence rates using random effects models and assessed statistical heterogeneity by visual examination of Forest plots, and by χ (2) and I(2) tests. RESULTS: We identified 1543 articles, of which nine articles met the study inclusion criteria. Five were case series, three were cohort studies, and one was a randomized controlled trial. Eight studies were from high-income countries, and one was from an upper middle-income country. Six studies reported results for pandemic influenza, and three reported seasonal influenza. Statistical heterogeneity was high for all outcomes, and methodologies and duration of surveillance varied considerably among studies; therefore, we did not perform meta-analyses. CONCLUSIONS: Study quality was very low according to GRADE criteria. More data on influenza disease incidence in pregnant women, particularly in low- and middle-income countries and for seasonal influenza disease, are needed to inform public health decision-making.